727 Increased serum levels of EBI3 are associated with poor outcome in hepatocellular carcinoma patients and SRF388, a first-in-class IL-27 blocking antibody, inhibits the growth of murine liver tumors. (9th November 2020) - Rausch, Matthew; Moodley, Devapregasan; Peluso, Marisa; Koseoglu, Secil; Hua, Jing; Tan, Gege; Masia, Ricard; Lee, Benjamin; Cousineau, Isabelle; Turcotte, Simon; Stagg, John; Palombella, Vito; et al.
Abstract : Background: IL-27 is a heterodimeric cytokine consisting of IL 27p28 and Epstein-Barr virus-induced gene 3 (EBI3) that binds the IL-27 receptor subunit alpha and glycoprotein 130. IL-27 is produced by activated macrophages and dendritic cells and limits the intensity and duration of immune responses in the tumor microenvironment by inducing the expression of immunoregulatory receptors (PD-L1, TIM3, LAG-3, TIGIT) and inhibiting production of proinflammatory cytokines (IFNγ, IL-17, TNFα). The IL-27 subunit EBI3 is elevated in plasma from patients with certain cancers including renal cell carcinoma, where it correlates with poor outcome. Based on high expression of IL-27 transcript in tumors from patients with hepatocellular carcinoma (HCC), the role of IL-27 was further explored in patient samples and a mouse model of HCC. Methods: Gene expression profiles from the Cancer Genome Atlas (TCGA) were analyzed to identify tumors with elevated IL-27 transcripts. Serum from patients with HCC was analyzed for levels of the IL-27 subunit EBI3. The ability of SRF388, a first-in-class IL-27-blocking antibody that binds to IL-27p28, to reverse IL-27-induced inhibition of cytokine production in human immune cell cultures from patients with HCC was assessed in vitro. Finally, the anti-tumor activity of SRF388 was assessed in an orthotopic murine model of HCC. Results: TCGA expression data revealed that IL-27p28 transcripts were elevated in tumors from patients with HCC relative to other indications. Serum levels of EBI3 were: 1) elevated in a subset of HCC patients; 2) inversely correlated with survival; 3) independent of serum alpha-fetoprotein levels; and 4) elevated in both hepatitis B/C virus positive and negative patients. Treatment with SRF388 stimulated increased cytokine production in activated peripheral blood mononuclear cells from patients with HCC that was further enhanced when combined with PD-1 blockade. Furthermore, SRF388 inhibited the growth of orthotopic Hepa1-6 liver tumors. mRNA transcriptional profiling of treated tumors revealed that SRF388 profoundly altered the transcriptional landscape in this model. In particular, treatment with SRF388 inhibited expression of immunoregulatory receptors PD-L1 and TIGIT, repressed transcripts associated with TGF-β signaling, and altered myeloid and natural killer cell transcripts. Conclusions: These data indicate that elevated IL-27 subunit EBI3 is a hallmark of HCC and is associated with poor outcomes in these patients. Blockade of IL-27 with SRF388, currently being evaluated in a Phase 1 clinical trial in patients with advanced solid tumors (NCT04374877 ), may represent a promising therapy for patients with HCC where it can potentiate anti-tumor immune responses.